Actividad y resultados a corto plazo del trasplante renal durante la pandemia COVID-19 - Calleja Hermosa, P. (Actas Urol Esp, 2021)
INTRODUCTION: During the COVID-19 pandemic, the national transplant activity has been reduced due to the overload of the health system and concern for patient safety in this situation. The aim of our work is to expose the activity of kidney transplantation in Cantabria during the state of alarm, as well as to assess the safety of the transplantation program. MATERIAL AND METHODS: Retrospective study of kidney transplants performed in our Center from the beginning of the state of alarm until the beginning of the lockdown easing in Cantabria. Descriptive analysis of the demographic data of recipients and their donors, intraoperative data and postoperative outcomes. Comparative analysis with the data of the same period in 2017-2019, by means of the χ(2) for categorical variables, Student's T and Mann-Whitney U tests in case of quantitative variables of normal and non-normal distribution, respectively. RESULTS: Fifteen kidney transplants were performed in the period described. Delayed renal function (DRF) was seen in 7.5% of patients, and 26.6% showed data of acute rejection; no patient presented COVID-19 disease. Comparative analysis showed a remarkable increase in the number of transplants in comparison with previous periods (15 vs 5.6), at the expense of donors from outside Cantabria (93.3%). We found no statistically significant differences in terms of cold ischemia time (p = 0.77), DRF (p = 0.73), need for dialysis (p = 0.54), or appearance of post-surgical complications (p = 0.61). CONCLUSIONS: The evolution of the pandemic in our region, and the adoption of strict protective measures has allowed the early and safe resumption of the renal transplantation program, increasing the number of transplants performed compared to previous years and maintaining comparable early post-operative results.